Seroepidemiology of Hepatitis E in Selected Population Groups in Croatia: A Prospective Pilot Study. (18th January 2016) - Vilibic‐Cavlek, T.; Vilibic, M.; Kolaric, B.; Jemersic, L.; Kucinar, J.; Barbic, L.; Bagaric, A.; Stevanovic, V.; Tabain, I.; Sviben, M.; Jukic, V.; Mlinaric‐Galinovic, G.
Summary: Hepatitis E has become an emerging infection in many European countries. We analysed the prevalence of hepatitis E virus (HEV) infection in selected population groups in Croatia. Overall HEV IgG seropositivity was 5.6%, while 1.9% participants showed IgM antibodies suggestive of recent infection. No IgM‐positive sample was positive for HEV RNA. HEV IgG antibodies were most prevalent in alcohol abusers (8.9%) and war veterans (8.6%), compared with 6.1% among injecting drug users and 2.7% in healthcare professionals. No individual with high‐risk sexual behaviour tested HEV seropositive. HEV IgG positivity increased significantly with age from 1.8% to 2.3% in individuals younger than 40 years to 11.3% in individuals older than 50 years ( P = 0.023). The mean age of HEV‐positive participants was significantly higher than that of HEV‐negative participants (50.9 ± 11.8 years versus 41.2 ± 11.8 years, P = 0.008). Seroprevalence rates were significantly higher in residents of suburban and rural areas compared with residents of urban areas (14.5% versus 2.5%, P = 0.003). Additionally, an increasing prevalence of HEV IgG antibodies was observed from 1.8% in participants living in families with two household members to 12.1% in those living with more than four members ( P = 0.046). Gender, marital status, educational level, sexual orientation, source of drinking water, history of blood transfusions, surgical procedures, tattooing and travelling were not associated with HEV seroprevalence. Logistic regression showed that living in suburban/rural areas was the main risk factor for HEV seropositivity (OR = 6.67; 95%CI = 1.89–25.0; AOR = 7.14, 95%CI = 1.89–25.0).